C-reactive protein and albumin kinetics after antibiotic therapy in community-acquired bloodstream infection. (June 2020) - Póvoa, Pedro; Garvik, Olav Sivertsen; Vinholt, Pernille Just; Pedersen, Court; Jensen, Thøger Gorm; Kolmos, Hans Jørn; Lassen, Annmarie Touborg; Gradel, Kim Oren
Highlights: Community-acquired bloodstream infection is associated with high morbidity and mortality. Serial C-reactive protein (CRP) measurements were analyzed. Individual patterns of CRP-ratio response identified short and long-term outcomes. The addition of albumin further increased this ability. Abstract: Objectives: We assessed C-reactive protein (CRP) and plasma albumin (PA) kinetics to evaluate community-acquired bloodstream infection (CA-BSI) patients' 1-year outcomes. Methods: Population-based study, with CRP and PA measurements on day 1 (D1) and D4. Relative CRP variations in relation to D1 CRP value were evaluated (CRP-ratio). Patients were classified as fast response, slow response, non-response, and biphasic response. Results: A total of 935 patients were included. At D4, the CRP-ratio was lower in survivors on D365 in comparison with D4–D30 non-survivors and D30–D365 non-survivors ( p < 0.001). In comparison with fast response patients, non-response and biphasic response patients had 2.74 and 5.29 increased risk, respectively, of death in D4–D30 and 2.77 and 3.16 increased risk, respectively, of death in D31–D365. PA levels remained roughly unchanged from D1–D4, but lower D1 PA predicted higher short and long-term mortality ( p < 0.001). The discriminative performance of the CRP-ratio and D1 PA to identify patients with poor short and long-term mortality after adjustments was acceptable (AUROC = 0.79). Conclusions: Serial CRP measurements at D1 and D4 after CA-BSI is clinically useful to identify patients with poor outcome. Individual patterns of CRP-ratio response with PA at D1 further refine our ability of predicting short or long-term mortality.